Rozsáhlý přehled dějin evropské integrace (Czech Journal of International Relations, 2000)
Pierre Gerbet: La construction de l' Europe. Imprimerie nationale, Paris 1999, 610 stran, ISBN 274330104X, ISSN 0246-4128.